Falling Felines and Fundamental Physics - Gbur, Greg (Yale University Press, 2019)
How do cats land on their feet? Discover how this question stumped brilliant minds and how its answer helped solve other seemingly impossible puzzles The question of how falling cats land on their feet has long intrigued humans. In this playful and eye opening history, physicist and cat parent Gregory Gbur explores how attempts to understand the cat righting reflex have provided crucial insights into puzzles in mathematics, geophysics, neuroscience, and human space exploration. The result is an engaging tumble through physics, physiology, photography, and robotics to uncover, through scientific debate, the secret of the acrobatic performance known as cat turning, the cat flip, and the cat twist. Readers learn the solution but also discover that the finer details still inspire heated arguments. As with other cat behavior, the more we investigate, the more surprises we discover.